A REVIEW AND DISCUSSION ON KNOWLEDGE SHARING, INNOVATION AND BUSINESS GROUP AFFILIATION - Özlem, Özen (Journal of Academic Researches and Studies, 2018)
Firms’ knowledge sharing activities include utilization of existing knowledge and creation of new knowledge with other firms. These knowledge flows refer to the exploitation and exploration of knowledge, which are defined as the different modes of organizational learning. Both types of knowledge sharing enhance existing innovations and allow for the development of new products or processes. However, explorative and exploitative knowledge sharing may have different impacts on innovation in various organizational settings. In developing economies, one of the important factors that may condition the role of knowledge sharing in innovation is the business group. Previous studies have investigated the knowledge sharing and innovation relations considering various settings and moderating factors; however, few have addressed the role of business groups. Therefore, this study discusses the effects of explorative, exploitative knowledge sharing on innovation and the role of business group affiliation in this relationship within the framework of the relevant literature. Accordingly, this study puts forward propositions which require further investigation. The propositions suggest that firms benefit from explorative and exploitative knowledge sharing in terms of innovation; however, business group affiliation might have positive or negative moderating role in this relationship
Keywords: Knowledge Sharing; Explorative-Exploitative Knowledge; Business Groups